EFFECT OF COPPER SULPHATE ON THE RESPIRATORY TISSUES OF DRAGON FLY NYMPHS (ANISOPTERA) AT VARIABLE TEMPERATURE - ANJALI SMITA; SUNITA DUTTA; ABHIJIT DUTTA (The Bioscan, 2010)
Assessment of toxicity on aquatic insects has gained significance for their suitability in bioassay studies. They also act as indicator species for many toxicants including heavy metals. In the present investigation dragonfly nymphs were selected as odonate larvae are important organisms in aquatic ecosystems. The present study tries to establish a correlation between the copper uptake and associated histological alterations and the subsequent changes in the respiratory tissues at different temperature ranges. It was found that accumulation of copper increased with duration of exposure till it reached a threshold limit beyond which the dragon fly nymphs failed to survive. The absorption of copper inside the body of the nymph also led to the deformities in the tracheal tissue as revealed by scanning electron micrograph investigation.